Bacterial keratitis: predisposing factors, clinical and microbiological review of 300 cases. Issue 7 (1st July 2003) - Bourcier, T; Thomas, F; Borderie, V; Chaumeil, C; Laroche, L
Abstract : Aim: To identify predisposing factors and to define clinical and microbiological characteristics of bacterial keratitis in current practice. Methods: A retrospective analysis of the hospital records of patients presenting with bacterial keratitis and treated at the Quinze-Vingts National Center of Ophthalmology, Paris, France, was performed during a 20 month period. A bacterial keratitis was defined as a suppurative corneal infiltrate and overlying epithelial defect associated with presence of bacteria on corneal scraping and/or that was cured with antibiotic therapy. Risk factors, clinical and microbiological data were collected. Results: 300 cases (291 patients) of presumed bacterial keratitis were included. Potential predisposing factors, usually multiple, were identified in 90.6% of cases. Contact lens wear was the main risk factor (50.3%). Trauma or a history of keratopathy was found in 15% and 21% of cases, respectively. An organism was identified in 201 eyes (68%). 83% of the infections involved Gram positive bacteria, 17% involved Gram negative bacteria, and 2% were polymicrobial. Gram negative bacteria were associated with severe anterior chamber inflammation (p=0.004), as well as greater surface of infiltrates (p=0.01). 99% of ulcers resolved with treatment, but only 60% of patients had visual acuity better than the level at admission, and 5% had very poor visual outcome. Conclusions: Contact lens wear is the most important risk factor. Most community acquired bacterial ulcers resolve with appropriate treatment.